An insight into in vitro antioxidant activity of Cantharellus cibarius hot water extract for the potential application in meat products. (September 2019) - Novakovic, S; Djekic, I; Vunduk, J; Klaus, A; Lorenzo, JM; Barba, F; Tomasevic, I
Abstract: The current research was undertaken to estimate the in vitro antioxidant activity of Cantharellus cibarius mushroom extracted by boiling in water for 30 minutes. Several previous studies have shown that the addition of edible mushrooms in meat products affects the reduction of lipid oxidation and prolongs the shelf-life of the final products. Antioxidant capacity of C. cibarius was measured using the following methods: reducing power ability, lipid peroxidation assay, cupric ion reducing antioxidant capacity (CUPRAC) and DPPH free radical scavenging activity. Reducing power and antioxidant activity assays of C. cibarius hot water extract showed low antioxidant activity. CUPRAC assay demonstrated positive effect only at the concentration of 10 mg/mL, whereas DPPH radical scavenging activity showed moderate antioxidant activity in comparison with culinary-medicinal mushrooms, with the effective concentration (EC50 ) from 7.41 mg/mL.